Effectiveness of exercise on fatigue in hemodialysis patients: a randomized controlled trial - Farzaneh Salehi; Mahlagha Dehghan; Parvin Mangolian Shahrbabaki; Mohammad Reza Ebadzadeh (BMC, 2020)
Abstract Background Hemodialysis is one of the common therapies in patients with end-stage renal disease. Even patients who receive regular treatment suffer from fatigue, which is one of the main factors leading to poor quality of life. This study aimed to determine the effectiveness of exercising on mini-bikes on fatigue in hemodialysis patients. Methods This study is a randomized controlled clinical trial. Thirty-seven hemodialysis patients participated in the study. The patients were randomly allocated to either the intervention group (n = 20) or the control group (n = 17). The participants in the intervention group exercised on mini-bikes for 20 min twice a week for 3 months. The patients' fatigue was measured four times during and after the intervention. Multidimensional Fatigue Inventory was used to measure the fatigue level. The total score in the MFI is 4 to 20 for each domain, with the resulting total fatigue score ranging from 20 to 100; thus, the higher the score, the higher the level of fatigue. Data were analyzed by SPSS 18. The repeated measures ANOVA was used to compare the fatigue scores within each group and between the groups at different times. Results The mean score of fatigue in the intervention group at the beginning was 58.80 ± 15.29, which steadily decreased to 58.78 ± 13.54, 58.75 ± 14.73, 54.20 ± 15.16, and 54.23 ± 13.60 for the 3 months of intervention and 1 month post-intervention, respectively. In contrast, in the control group, this score was 62.53 ± 16.32 in the beginning, increasing to 64.03 ± 13.91, 64.22 ± 13.07, 69.53 ± 9.22, for the 3 months of intervention and 70.34 ± 7.69 one-month post-intervention. There were significant differences between the intervention group and the control group in the third month (P = 0.001) and 1 month after the intervention (P < 0.001). Conclusions The results showed that rehabilitation through exercising using mini-bikes had a significant impact on preventing further fatigue build-up in hemodialysis patients, making the mini-bike an effective non-pharmaceutical intervention preventing the increase in fatigue experienced by patients undergoing hemodialysis. Trial registration Iranian Registry of Clinical Trials: IRCT20180314039100N1 . Registered 10 June 2018.